Automated quantitation of fetomaternal hemorrhage by flow cytometry for HbF‐containing fetal red blood cells using probability state modeling. Issue 5 (22nd March 2013) - Wong, L.; Hunsberger, B. C.; Bruce Bagwell, C.; Davis, B. H.
Summary: Background: Flow cytometric methods (FCMs) are the contemporary standard for fetal red blood cell (RBC) quantitation and fetomaternal hemorrhage (FMH) detection. FCM provides greater sensitivity and repeatability relative to manual microscopic Kleihauer–Betke methods. FCM assays are not totally objective, employing subjective manual gating of fetal RBCs with measureable interobserver imprecision. We investigated Probability State Modeling to automate analysis of fetal RBCs using an assay for hemoglobin F (HbF)–containing RBCs. Methods: Two hundred human bloods were processed using the FMH QuikQuant™ assay (Trillium Diagnostics, Brewer, ME, USA). A Probability State Model (PSM) was designed to enumerate fetal RBCs by selecting the three RBCs subpopulation based on differences in intensity levels of several parameters. The GemStone™ program uses a PSM that requires no operator intervention. Routine manual analysis by experienced users was performed, along with replicate analyses for both methods. Results: The PSM by GemStone™ correlates strongly with the expert manual analysis, r 2  = 0.9986. The mean absolute difference of the FMH results between GemStone™ and manual 'expert' analysis was 0.04% with no intermethod bias detected. Manual gating demonstrated coefficient of variations (CVs) of 10.6% for intra‐analyst replicates and 22.6% for interanalyst imprecision. The interanalyst agreement in GemStone™ is a perfect correlation, r 2  = 1.00, and no imprecision with a 0.00% CV. Conclusion: Automated PSM analysis of fetal RBCs strongly correlates with expert traditional manual analysis. PSM enumerates fetal RBCs accurately with significantly greater objectivity and lower imprecision than the traditional manual gating method. Thus, PSM provides a means to markedly improve interlaboratory variance with FMH assays based upon subjective gating strategies.